PERAN PUBLIC RELATION DALAM PROGRAM LARASITA BADAN PERTANAHAN KABUPATEN TIMOR TENGAH UTARA DI KELURAHAN KEFA TENGAH - Nubatonis, Servince Imelda (Interaksi: Jurnal Ilmu Komunikasi, 2015)
Abstract:Goal of the research to find out the role and planning models National Land Agency located in TTU regency (BPN TTU). This research as an evaluating BPN TTU activities in the management organization to goal the point of organization.Research method is description cualitative with National Land Agency located in TTU regency by the subject research. The theories to analisist the research result are four role by Cutlip, Center & Broom and six models planing PR by Anggoro.The result of research just find two role PR BPN apply those are expert prescriber and communication fasilitator. Before activites the project of Larasita BPN TTU apply also like Anggoro Theories.